Freshwater environment affects growth rate and muscle fibre recruitment in seawater stages of Atlantic salmon ( Salmo salar L.) - Johnston, Ian Alistair; Manthri, S; Alderson, R; Smart, A; Campbell, P; Nickell, D; Robertson, B; Paxton, CGM; Burt, Mary Louise (Journal of Experimental Biology, 2003)
The influence of freshwater environment on muscle growth in seawater was investigated in an inbred population of farmed Atlantic salmon (Salmo salar L.). The offspring from a minimum of 64 families per group were incubated at either ambient temperature (ambient treatment) or in heated water (heated treatment). Growth was investigated using a mixed-effect statistical model with repeated measures, which included terms for treatment effect and random fish effects for individual growth rate (alpha) and the instantaneous growth rate per unit change in temperature (gamma). Prior to seawater transfer, fish were heavier in the heated (61.6+/-1.0 g; N=298) than in the ambient (34.1+/-0.4 g; N=206) treatments, reflecting their greater growth opportunity: 4872 degree-days and 4281 degree-days, respectively. However, the subsequent growth rate of the heated group was lower, such that treatments had a similar body mass (3.7-3.9 kg) after approximately 450 days in seawater. The total cross-sectional area of fast muscle and the number (FN) and size distribution of the fibres was determined in a subset of the fish. We tested the hypothesis that freshwater temperature regime affected the rate of recruitment and hypertrophy of muscle fibres. There were differences in FN between treatments and a significant age x treatment interaction but no significant cage effect (ANOVA). Cessation of fibre recruitment was identified by the absence of fibres of <10 mum diameter. The maximum fibre number was 22.4% more in the ambient (9.3x10(5)+/-2.0x10(4)) than in the heated (7.6x10(5)+/-1.5x10(4)) treatments (N=44 and 40 fish, respectively; P<0.001). For fish that had completed fibre recruitment, there was a significant correlation between FN and individual growth rate, explaining 35% of the total variation. The density of myogenic progenitor cells was quantified using an antibody to c-met and was approximately 2-fold higher in the ambient than in the heated group, equivalent to 2-3% of the total muscle nuclei. The number of myonuclei in ...